Trace copper-mediated asexual development via a superoxide dismutase and induction of AobrlA in Aspergillus oryzae - Katayama, Takuya; Maruyama, Jun-ichi (Frontiers in Microbiology, 2023)
The filamentous fungus Aspergillus oryzae, in which sexual reproduction remains to be discovered, proliferates mainly via asexual spores (conidia). Therefore, despite its industrial importance in food fermentation and recombinant protein production, breeding beneficial strains by genetic crosses is difficult. In Aspergillus flavus, which is genetically close to A. oryzae, structures known as sclerotia are formed asexually, but they are also related to sexual development. Sclerotia are observed in some A. oryzae strains, although no sclerotia formation has been reported in most strains. A better understanding of the regulatory mechanisms underlying sclerotia formation in A. oryzae may contribute to discover its sexual development. Some factors involved in sclerotia formation have been previously identified, but their regulatory mechanisms have not been well studied in A. oryzae. In this study, we found that copper strongly inhibited sclerotia formation and induced conidiation. Deletion of AobrlA encoding a core regulator of conidiation and ecdR involved in transcriptional induction of AobrlA suppressed the copper-mediated inhibition of sclerotia formation, suggesting that AobrlA induction in response to copper leads not only to conidiation but also to inhibition of sclerotia formation. In addition, deletion of the copper-dependent superoxide dismutase (SOD) gene and its copper chaperone gene partially suppressed such copper-mediated induction of conidiation and inhibition of sclerotia formation, indicating that copper regulates asexual development via the copper-dependent SOD. Taken together, our results demonstrate that copper regulates asexual development, such as sclerotia formation and conidiation, via the copper-dependent SOD and transcriptional induction of AobrlA in A. oryzae.